1994
DOI: 10.1200/jco.1994.12.3.617
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen: is it useful in the treatment of patients with metastatic melanoma?

Abstract: While TAM as a single agent is minimally active in treating patients with metastatic melanoma, when it is combined with DTIC, BCNU, and DDP, a marked improvement in the overall response rate is observed. Although a prospective randomized trial has yet to be completed, it appears that this four-drug combination has a higher overall and complete response (CR) rate when compared with single-agent DTIC. In light of the relatively modest toxicity observed with this regimen, the combination of DBDT represents a reas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…At present it is not known whether glycolipids influence P-gp activity or whether P-gp, in some fashion, regulates glycolipid metabolism. On the other hand, regarding estrogen receptor-independent actions (51)(52)(53)(54), tamoxifen has long been viewed with curiosity, particularly with reference to reversal of MDR (55) and synergy in combination chemotherapy (56,57). In view of the data presented herein, it is suggested that tamoxifen can increase cellular susceptibility to chemotherapeutic agents via a glycosphingolipid-governed avenue, and we propose that tamoxifen-induced MDR reversal is, in part, dependent on finetuned regulation of ceramide metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…At present it is not known whether glycolipids influence P-gp activity or whether P-gp, in some fashion, regulates glycolipid metabolism. On the other hand, regarding estrogen receptor-independent actions (51)(52)(53)(54), tamoxifen has long been viewed with curiosity, particularly with reference to reversal of MDR (55) and synergy in combination chemotherapy (56,57). In view of the data presented herein, it is suggested that tamoxifen can increase cellular susceptibility to chemotherapeutic agents via a glycosphingolipid-governed avenue, and we propose that tamoxifen-induced MDR reversal is, in part, dependent on finetuned regulation of ceramide metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…nation for the results of the clinical trial mentioned earlier evaluating the ability of TAM to overcome established DDP resistance. 6 In DDP-sensitive mela-…”
Section: Eligibility Requirementsmentioning
confidence: 99%
“…Additional clinical trials conducted by the authors have demonstrated that TAM 1) TAM/DDP synergy is dependent on a tumor cell's innate sensitivity to TAM; 2) Although DDP sensitivity can overcome established clinical resistance to DDP. 6 In contrast, Rusthoven et al recently reported the is important, it plays a relatively minor role and can be overcome by increasing the concentration of TAM; results of a prospective, randomized, placebo-controlled trial in which the response rate of the original and 3) TAM resistance results in complete loss of synergy, regardless of the concentrations of either TAM Dartmouth regimen was compared with the same regimen without TAM in patients with metastatic melaor DDP employed. Therefore, the authors hypothesized that the clinical use of higher doses of TAM will noma.…”
mentioning
confidence: 99%
“…Dacarbazine (DTIC), the most active single agent in the treatment of melanoma, can be expected to yield a response rate of about 20% (McClay and McClay, 1996). Even though most trials of combination chemotherapy for the treatment of metastatic melanoma clearly have not been superior to DTIC alone, the combination of carmustine (BCNU), DTIC, cisplatin, and tamoxifen has produced significant antitumour responses in up to 50% of patients (McClay and McClay, 1994;Middleton et al, 2000;Richards et al, 1992). A further increase in the rate of objective responses may be achieved by introducing cytokines into the therapeutic regimens, with interleukin-2 (IL-2) and interferon alpha (IFN-a) being the most widely acclaimed.…”
mentioning
confidence: 99%